MODERATION OF GOVERNMENT ACCOUNTING STANDARDS IN THE RELATIONSHIP OF PUBLIC ACCOUNTABILITY, PUBLIC TRANSPARENCY AND OVERSIGHT OF APBD MANAGEMENT - Hasibuan, Ira Maulida Sari; Irfan, Irfan; Sari, Maya; Sari, Eka Nurmala (Kajian Akuntansi, 2024)
The purpose of this research is to test and analyze the influence of public accountability, public transparency, and supervision of APBD management with government accounting standards as moderator variables on the Labuhanbatu district government directly and indirectly. The approach used in this research is explanatory. The population in this study was 45 local government organizations in Labuhanbatu district, resulting in a total of 135 respondents. Data collection techniques in this research used questionnaires and document study. The data analysis technique in this research uses a quantitative approach using statistical analysis with Outer Model Analysis Test, Inner Model Analysis, and Hypothesis Testing. Data management in this research uses the SEM-PLS software program. The results of this research prove that accountability, transparency, supervision, the public have a significant influence on the management of the Labuhanbatu Regency APBD, and Government accounting standards are able to moderate the influence of public accountability and supervision on APBD management, but government accounting standards are unable to moderate the influence of public transparency on APBD management. Keywords     : Public    Accountability,   Public    Transparency,    Government Accounting Standards, Budget Management.